The Influence of Entrepreneurship Education Level and Technological Progress on Entrepreneurial Interest in the Millennial Generation - Andi Tenri Ampa (Cita konsultindo, 2023)
This research was conducted with the aim of determining the influence of the level of entrepreneurship education and technological advances on interest in entrepreneurship in the millennial generation. The data collection technique in this research is in the form of a questionnaire. In this research, the method used was a quantitative descriptive method with a population of 30 students at Makassar State University as the millennial generation. The data analysis technique uses multiple linear regression analysis models, F test, t test, and coefficient of determination (R2) with the SPSS 21 application. The results show that: (1) entrepreneurship education has a positive and significant effect on interest in entrepreneurship in the millennial generation; (2) technological advances have a positive and significant effect on the interest in entrepreneurship in the millennial generation